Gender, Reading, and Truth in the Twelfth Century : the Woman in the Mirror. - Powell, Morgan (Medieval Media and Culture Ser., 2020)
Argues that a reading act conceived of as female lies behind the polysemic identification of women as the audience of new media in the twelfth century.